STYLE AND MOTIVATION VARIABLE AS FACTORS AFFECTING EMPLOYEE COMMITMENT - Venantius Mardi Widyadmono; Adhatu Achsa (Program Studi Magister Manajemen, 2023)
The purpose of this study is to ascertain how PT Indogrosir Bandar Lampung's leadership and motivational practices affect employee commitment. This study employs a quantitative methodology. The TCR approach was employed by the authors to examine the data that had been gathered for this investigation. This study employs SPSS 23 software to simplify data analysis and statistics as a calculating technique for its analysis. According to the study analysis's findings, PT Indogrosir Bandar Lampung's leadership style and motivation have a big impact on staff commitment, In order to strengthen employee commitment, there is still a need for specific adjustments to be made by the management as well as the organization's leadership in the development of leadership style and motivation.